An Experimental Study to Analyze the Role of planter pressure system (sensor plate) in Neurological Patients for Diagnostic Cum Planning Management in Rehabilitation - Vashi, Achalkumar; Menaria, Shubham; khan, Jafar; Annamalai, KM.; Lohar, Deepak; Quershi, Abid R; Balala, Dipika; Rai, Richa Hirendra (Journal of Neonatal Surgery, 2025)
The role of sensor plate technology in neurological rehabilitation has gained significant attention for its potential to improve functional outcomes. This study aimed to evaluate the effectiveness of sensor plates in improving the Foot Function Index (FFI) in neurological patients. A comparative experimental design was employed, involving 50 participants divided into two groups: a trial group (n=25) where sensor plates were utilized for assessment and rehabilitation, and a control group (n=25) where traditional rehabilitation methods were used without sensor plates. Participants were assessed pre- and post-intervention over 12 weeks, and the data were analyzed using paired and independent t-tests. Results revealed a statistically significant improvement in FFI scores in the trial group compared to the control group (p < 0.05), demonstrating the efficacy of sensor plates in enhancing mobility and functional outcomes. This study highlights the importance of integrating advanced technologies like sensor plates into rehabilitation programs to improve patient outcomes. The findings support the adoption of sensor plates in clinical practice, offering a more precise and effective approach to neurological rehabilitation. Further research with larger sample sizes and diverse populations is recommended to validate these findings and expand the applicability of sensor-based technologies